ISOLATION, CHARACTERIZATION AND SCREENING OF COMPETENT FUNGAL ISOLATES FROM TEXTILE SLUDGE FOR DECOLORIZATION OF SELECTED SYNTHETIC DYES - C. AGNES MARIYA DORTHY; RAJESHWARI SIVARAJ (International Journal of Pharma and Bio Sciences, 2013)
Textile industry is predominant in employing dyes and chemicals, cause for environmental degradation and human maladies. Synthetic dyes have an adverse effect on the aquatic ecosystem and their toxic substance has to be removed from the effluent before their exoneration. This research paper aimed, to isolate and screen the competent fungi from textile sludge capable of decolorizing broad spectrum of dyes. Twelve fungal isolates from sludge were preliminary screened by using Czapek Dox agar with 100 mg/ml of dyes. Six fungal isolates have shown decolorization of all three synthetic dyes. Among fungal isolates, Aspergillus flavus showed maximum growth (7.33±1.30) and in plate assay, Aspergillus flavus showed maximum decolorization zone (6.20 ±1.58) in Reactive violet-2RL followed by Acidic Blue-G and Direct Green-B, Aspergillus fumigatus showed 5.33±0.42 and 4.73±0.23. This research work reports that fungi offer an easy, cost effective method and could be used in development of an effective biotreatment method for the removal of dyes from textile effluent.